2014
DOI: 10.1063/1.4871383
|View full text |Cite
|
Sign up to set email alerts
|

Using giant magneto resistance stripes to efficiently generate direct voltage signals from alternating current excitations

Abstract: We have developed all metal spintronic devices which convert an alternating current (AC) in-plane current into a direct current (DC) voltage without using external magnetic fields. The devices are based on the modulation of the magnetization of the free magnetic layer in an exchange biased giant magneto resistance nanowire by the current-induced Oersted field. They can be operated at frequencies extending into the GHz range, and the resistance is easily tunable by changing the wire length. The devices can be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…4.6. It should be noted that an analogous diode effect due to GMR has also been observed [247][248][249]. Table 7 summarizes some of the key studies in the development of the spin transfer based spin diode and MTJ rectification and Fig.…”
Section: Spin-transfer Torque Rectification In Magnetic Tunnel Junctionsmentioning
confidence: 95%
See 1 more Smart Citation
“…4.6. It should be noted that an analogous diode effect due to GMR has also been observed [247][248][249]. Table 7 summarizes some of the key studies in the development of the spin transfer based spin diode and MTJ rectification and Fig.…”
Section: Spin-transfer Torque Rectification In Magnetic Tunnel Junctionsmentioning
confidence: 95%
“…One downside to MTJ based sensing is the complex device fabrication required. In this regard the recently realized GMR based diode effect may prove advantageous [247,248].…”
Section: Spintronic Microwave Sensing and Imagingmentioning
confidence: 99%
“…In this paper we report on a spin diode effect in an exchange-biased Spin Valve Giant Magnetoresistance (SV-GMR) strip, which is an alternative to AMR-or MTJ-based devices. Very recently, a similar SV-GMR strip has been investigated by Kleinlein et al 29 The authors, however, focused their attention mainly on its enhanced detection sensitivity when compared to an AMR-based device.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that the giant magnetoresistive (GMR) microstripe exhibits more than ten times higher sensitivity compared with the FM microstripe. 11,22,23 These investigations have revealed the influencing factors of V DC such as the stripe width 23 and the interlayer coupling. 11,24 Changing the magnitude and the direction of the in-plane (IP) and out-of-plane (OOP) magnetic fields was reported to be effective in tailoring V DC and at resonant frequency (f R ) in MTJ-based STMD.…”
mentioning
confidence: 99%